MAKNA DAN HAKIKAT PENDIDIKAN BIDANG POLITIK DALAM ALQURAN - Aslan Aslan (Cross-border, 2019)
Education is not only in the social and cultural scope, but covers all fields, including the political field. The study of this research is literature by searching related literature and looking for research findings from this study. The findings of this study that; First, politics teaches us about power, which is obtained by education. Second, the Qur'an also teaches humans about good politics without bringing down opponents.